Digital Escape Room, Using Genial.Ly and A Breakout to Learn Algebra at Secondary Education Level in Spain - Cristina Jiménez; Nuria Arís; Ángel Alberto Magreñán Ruiz; Lara Orcos (MDPI AG, 2020)
One of the main objectives in mathematics education is to motivate students due to the fact that their interest in this area is often very low. The use of different technologies, as well as gamification in the classroom, can help us to meet this goal. In this case, it is presented the use of two techniques, which are a digital escape room, using Genial.ly and a breakout, for learning algebra in the third course of secondary education. To carry out the experience, a comparison of the course 2018/2019 and the course 2019/2020 is made. Students of both courses completed an exam of algebraic fractions and then an equations exam; the exams were done in the course 2019/2020 taken after having used the techniques. The results show that there are low significant differences between both courses in the algebraic fractions exam qualifications, but those of the equations exam were significant, with a difference of almost two points, which led us to conclude that the use of this techniques improved the qualifications of students. Finally, the perception that students had of the experience was very positive, as shown by the data obtained and allowed them to improve their knowledge as well as their motivation and teamwork.